1976
DOI: 10.1002/kin.550080606
|View full text |Cite
|
Sign up to set email alerts
|

The photochemistry of hexafluoroacetylacetone in the vapour phase. Occurrence of a novel HF elimination reaction

Abstract: Photolysis of the vapour of hexafluoroacetylacetone HFAA in its enolic form involves decomposition by two independent primary processes, one of which is a novel elimination of H F giving 2,2-difluoro-2,3-dihydro-5trifluoromethylfuran-3-one:The HF is not vibrationally excited. CF2 radicals which, if HFAA is present, undergo an insertion into the enolic OH bond, Photolysis of the cyclic product of reaction ( 5 ) yieldsCF, + CF,C=CHCOCF, -+ CF,C=CHCOCFx I OCF,H I OH The infrared, ultraviolet, nuclear magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The transition state for the rotation, which is the rate limiting step, lies energetically below the neutral HFAAc, making this rotation readily available at 0 eV incident electron energy. In analogy to the mechanism proposed by Basset and Whittle, 35 this rotation is proposed as a prerequisite to the loss of HF upon DEA.…”
Section: Multiple Bond Ruptures and Rearrangement Reactionsmentioning
confidence: 78%
See 1 more Smart Citation
“…The transition state for the rotation, which is the rate limiting step, lies energetically below the neutral HFAAc, making this rotation readily available at 0 eV incident electron energy. In analogy to the mechanism proposed by Basset and Whittle, 35 this rotation is proposed as a prerequisite to the loss of HF upon DEA.…”
Section: Multiple Bond Ruptures and Rearrangement Reactionsmentioning
confidence: 78%
“…13,38 There we showed that the existence of intramolecular X-H/F-C hydrogen bonds is a prerequisite for the formation of HF. In fact, for the observed HF loss in the photolysis study, Basset and Whittle 35 argued that aer photon absorption, the excited HFAAc undergoes conformational changes through rotation. Hence, bringing the keto-CF 3 group in close vicinity to the enolic hydrogen, thus ensuring the conditions for HF formation and that of the furanone shown in Fig.…”
Section: Multiple Bond Ruptures and Rearrangement Reactionsmentioning
confidence: 99%
“…There has been little work reported on the thermal decomposition of 2. There is, however, a substantial of work on CVD related investigations of hfacH over metal and metal oxide surfaces, [42][43][44][45][46][47][48] while the photolysis study by Bassett and Whittle 49 is the only account of the homogeneous decomposition of 2. Photolysis of the predominant enol form of 2 occurred with a novel HF elimination to yield 2,2-difluoro-5-(trifluoromethyl)furan-3(2H)-one (DHTF, 7).…”
Section: Resultsmentioning
confidence: 99%
“…The mass spectrum of the product eluted at 1.61 min was identical with the mass spectra obtained from the decomposition of a range of oxovanadium(IV) hfac complexes, UO 2 (hfac) 2 , and from UV photolysis of 2. 49,51,52 This compound was identified as 7. The mass spectrum of the compound eluted at 1.65 min was attributed, upon comparison with mass spectral data obtained by Bassett and Whittle, to 8, that is, the product resulting from CF 2 carbene insertion into the O-H bond of a hfacH molecule following UV photolysis.…”
Section: Resultsmentioning
confidence: 99%
“…• C, decomposition of hfa [62][63][64] (and possibly also of the complexes [48]) sets in, resulting in non-chemically selective aerosol transport. The 3d members of neighboring groups 5 and 6, i.e., Nb and Mo, have been shown to be transported as hfa complexes to a significantly smaller extent, if at all.…”
Section: Transport Timementioning
confidence: 99%